Bovine pericardium membrane as new tool for mesenchymal stem cells commitment. (15th August 2019) - Ferroni, Letizia; Gardin, Chiara; Bellin, Gloria; Vindigni, Vincenzo; Mortellaro, Carmen; Zavan, Barbara
Abstract: Acellular matrices are widespread biomaterials used in surgical practice as tissue reinforcement and anatomical support to favor tissue regeneration. It is clear that a fundamental role in the regeneration of tissue is played by cell–material interaction. In this work, the interaction between a bovine pericardium membrane and human adult stem cells was investigated by microscopy analysis and gene expression analysis. Parallel cell cultures were prepared on the pericardium membrane or tissue culture plate. They were incubated in basal growth medium or in adipogenic differentiation medium to perform experiments on the seventh and the 14th day of culture. Results demonstrated that the membrane allows cell viability, adhesion, and proliferation of human stem cells. During adipogenic commitment on the membrane, the accumulation of cytoplasmatic lipid droplets and the expression of adipogenic gene PPARG, CEBPA, GLUT4, FABP4, and ADIPOQ were detected. Concurrently, a downregulation of mesenchymal stem cell gene CD29, CD90, and CD105 was detected. In basal medium, the adipogenic gene expression was upregulated, whereas the mesenchymal markers were indifferently expressed. These findings suggest that the bovine pericardium membrane is a biocompatible matrix and that their rough surface allows cell adhesion, spreading, and proliferation. The surface morphology activates mechanochemical signals that stimulate the adipogenic commitment of stem cells in basal medium and potentiate their commitment in adipogenic differentiation medium.